Impact of the first phase of COVID-19 pandemic on childhood routine immunisation services in Nepal: a qualitative study on the perspectives of service providers and users - Asmita Priyadarshini Khatiwada; Smriti Maskey; Nistha Shrestha; Sunil Shrestha; Saval Khanal; K C Bhuvan; Vibhu Paudyal (Taylor & Francis Group, 2021)
Background The COVID-19 pandemic has disproportionately affected all essential healthcare services delivery in low-resource settings. This study aimed to explore the challenges and experiences of providers and users of childhood immunisation services in Nepal during the COVID-19 pandemic. Methods Semi-structured qualitative interviews were conducted with childhood immunisation service providers and users (i.e., parents of children) from Kathmandu valley, Nepal. All interviews were conducted through phone or internet-based tools, such as Zoom, WhatsApp, and messenger. All interviews were audio-recorded, transcribed verbatim, and analysed using theme-based content analysis in an Excel spreadsheet. Results A total of 15 participants (n = 7 service providers and n = 8 service users) participated. Six themes were identified, namely: (1) impact of COVID-19 and lockdown on childhood immunisation services; (2) motivation and resilience for childhood immunisation; (3) Biosafety practices and Personal Protective Equipment (PPE) availability during the COVID-19 pandemic; (4) service adjustments and guidelines during pandemic; (5) availability of vaccines; and (6) immunisation program resilience in view of COVID-19. Service providers mentioned facing disruptions in services and some parents had decided to delay scheduled immunisation. However, most service providers showed determinations to deliver the services with high morale, while most service users reported taking their children for immunisation. Families migrating from urban to rural areas during the pandemic led to service providers having no means to confirm complete immunisation of migrating children. Service providers also experienced lack of adequate guidance to deal with the pandemic and personal protective equipment to protect themselves and service users. Conclusion Despite experiencing disruptions in childhood immunisation service due to the COVID-19 pandemic, service users and providers were determined to vaccinate the children. There is an urgent need for effective preparedness plans to be in place to address the observed barriers and to ensure resilient immunisation services during ongoing and future pandemics.